Controlling jako nowoczesne narzędzie zarządzania przedsiębiorstwem - Karwacki, Piotr (Controlling as a modern management tool, 2005)
The present day managers choosing rational management methods should have adequate planning, controlling and steering instruments at disposal using modem information systems. Modem and highly effective management instrument adding management functions is controlling. In this paper author presents some general backgrounds of one method developing organization, it means controlling. This method gives possibilities for holistic view for enterprises’ problems and simultaneously gives possibilities to improve effectiveness present day operating organizations
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 270-279